Human Capital: Driving Force of Economic Growth in Selected Emergine Economies - Awan , Abdul Ghafoor (Global Disclosure of Economics and Business, 2012)
Human capital is the stock of competencies, knowledge and personality attributes deem vital to produce economic value. It is the attributes gained by a worker through education, training and experience. According to modern growth theory, the accumulation of human capital is an important contributor to economic growth. Numerous cross-country studies extensively explore whether educational attainment can contribute significantly to the production of overall output in an economy. The objective of this paper is to investigate the role of human capital in the fast economic growth of BRIC countries like Brazil, Russia, India and China during 2000-2011 and to assess sustainability of growth in future. The study is descriptive in nature because it mostly involves the description of the situation of human capital in the BRIC countries and measuring change in the selected important variables that is human capital and policy initiative and its effects on the BRIC economies. As the change in the selected variables is clearly visible there is no need to use regression analysis technique. The author has applied statistical techniques such as trend analysis, content analysis and ratio analysis to measure change in the selected variables wherever it is necessary. The findings of the study are interesting and divergent because the human capital development has played a vital role in the fast economic growth of China, India and Brazil while Russia, which was endowed with human capital right from the beginning, could not materialize the potential of human capital during its transition period from planned economy to market economy since 1990s, which is very much surprising. This appears the policy failure to capitalize the valuable human capital to accelerate economic growth. It has resulted in the scaling down of Russia to middle income economy. In contrast, India, China and Brazil have been fully utilizing their human capital potential by following human developing policies and this factor not only has triggered their economic growth but also alleviated poverty in there. GEL Classification Code: F43; J24